Production Engineering Research and Development - Merklein, Marion; Hagenah, Hinnerk; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The journal reports peer reviewed results of latest research in industrial engineering, production engineering and industrial organization. The high level and focus on both the scientific as well as the practical impact of the selected papers will bridge the gap between research and successful industrial application. Researchers in production engineering as well as in operation management and supply chain organization will find recent valuable developments. The main topics span from novel production processes via computer aided engineering to process chain and factory management. Frequently published key note papers provide succinct reviews on the recent progress in particular research areas.
Keywords: Production management; Industrial engineering; Production engineering; Industrial and Production Engineering; Production